Incentives of Health Care Expenditure - Siljander, Eero (Farmeconomia. Health economics and therapeutic pathways, 2012)
The incentives of health care expenditure (HCE) have been a topic of discussion in the USA (Obama reforms) and in Europe (adjustment to debt crisis). There are competing views of institutional versus GDP (unit income elasticity) and productivity related factors of growth of expenditure. However ageing of populations, technology change and economic incentives related to institutions are also key drivers of growth according to the OECD and EU’s AWG committee. Simulation models have been developed to forecast the growth of social expenditure (including HCEs) to 2050. In this article we take a historical perspective to look at the institutional structures and their relationship to HCE growth. When controlling for age structure, price developments, doctor density and in-patient and public shares of expenditures, we find that fee-for-service in primary care, is according to the results, in at least 20 percent more costly than capitation or salary remuneration. Capitation and salary (or wage) remuneration are at same cost levels in primary care. However we did not find the cost lowering effect for gatekeeping which could have been expected based on previous literature. Global budgeting 30 (partly DRG based) percent less costly in specialized care than other reimbursement schemes like open contracting or volume based reimbursement. However the public integration of purchaser and provider cost seems to result to about 20 higher than public reimbursement or public contracting. Increasing the number of doctors or public financing share results in increased HCEs. Therefore expanding public reimbursement share of health services seems to lead to higher HCE. On the contrary, the in-patient share reduced expenditures. Compared to the previous literature, the finding on institutional dummies is in line with similar modeling papers. However the results for public expansion of services is a contrary one to previous works on the subject. The median lag length of adjustment is 6.6 years or 26 quarters for countries to move half way to the eventual equilibrium in HCE/GDP-ratios in response to a shock in demand factors which indicates “hysteresis” in demand.